2018
DOI: 10.5001/omj.2018.71
|View full text |Cite
|
Sign up to set email alerts
|

Value of Ultrasound in the Detection of Benign and Malignant Breast Diseases: A Diagnostic Accuracy Study

Abstract: Mammography is the best technique for screening and identifying patients with non-mass-like breast lesions and microcalcifications. Considering the false positive and false-negative results, ultrasound is not a perfect screening modality. Future studies are recommended to study the value of ultrasound in the detection of high-risk breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Therefore, such limitation of mammography may limit the its screening efficacy in population having a high proportion of dense breast. Ultrasound has the potential of detecting small nodules and is also widely accessible and affordable in countries having limited and unbalanced health resources (810). The current breast cancer screening guidelines recommended that ultrasound could be served as an auxiliary screening method to mammography (5, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such limitation of mammography may limit the its screening efficacy in population having a high proportion of dense breast. Ultrasound has the potential of detecting small nodules and is also widely accessible and affordable in countries having limited and unbalanced health resources (810). The current breast cancer screening guidelines recommended that ultrasound could be served as an auxiliary screening method to mammography (5, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Gharekhanloo et al (2018) conducted a study among 203 females and reported that the most common location of both benign and malignant breast masses detected on ultrasound was the upper outer quadrant. 2 However, the current study revealed that overlapping lesions were the most common site of breast masses, followed by the upper outer quadrant.…”
Section: Discussionmentioning
confidence: 50%
“…Data on sociodemographic characteristics, clinical presentation, breast ultrasound findings, and patient risk factors for breast cancer were collected through a researcher- designed checklist after reviewing similar studies. 2 , 4 , 12 , 15 Moreover, histopathological results were also reported, if performed. The authors collected the data by filling the checklists at the PHC center of IAU between January and March 2020.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations